Determinasi Minat Berinvestasi Di Pasar Modal (Studi Kasus Mahasiswa Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung) - Danang Wahyu Pranowo; Nafik Umurul Hadi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Technological advances in the 21st century are increasingly rapid. Technological advances also occur in the field of investment. Purchasing shares in the past was done face-to-face at the Indonesia Stock Exchange and still used paper and blackboards to make transactions. nowadays we don't need to bother because buying and selling shares can be done online anytime and anywhere using a device. Although there are many conveniences and education in stock transactions, the consequences of a study directed by specialists, as a matter of fact within the scope of Bhinneka PGRI University show that more students know about mutual fund investment than stock investment. Through this study, the researcher intends to find out whether Technological Progress and Investment Knowledge affect the interest in investing of Economics Education Study Programme Students at Bhinneka PGRI University in the capital market. This research is supported by data analysis software called Partial Least Square. this research shows that technological advances and investment knowledge have a positive effect on investment interest.Â